ANALYZING THE ROLE OF HYPER-PERSONALIZED CONTENT AND ARTIFICIAL INTELLIGENCE IN ENHANCING CONSUMER ENGAGEMENT AND PURCHASE DECISIONS THROUGH A SYSTEMATIC LITERATURE REVIEW - Ahmad Izzuddin; Vesa Karsi Sukmawati (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This study examines the role of hyper-personalized content and artificial intelligence in enhancing consumer engagement and purchase decisions in digital marketing. The rapid growth of data-driven technologies has transformed marketing practices, yet inconsistencies remain regarding how personalization and AI contribute to meaningful engagement and decision-making. This study aims to synthesize existing literature to provide a comprehensive understanding of these relationships. Method: A Systematic Literature Review approach was employed, following PRISMA guidelines, with data collected from Scopus, Web of Science, and ScienceDirect databases covering publications from 2020 to 2025. Selected studies were analyzed using qualitative content analysis and thematic coding to identify patterns, trends, and research gaps. Results: The findings indicate that AI enhances content relevance, targeting accuracy, and engagement quality, while hyper-personalization strengthens cognitive and emotional connections with consumers. However, excessive personalization may raise privacy concerns and reduce trust, limiting effectiveness. Engagement emerges as a critical pathway linking AI-driven strategies with purchase decisions, although outcomes depend on contextual and behavioral factors. This study highlights the importance of balancing technological innovation with ethical considerations to achieve sustainable marketing performance. Future research should explore cross-cultural contexts, longitudinal designs, and hybrid analytical approaches to deepen understanding of evolving consumer behavior. Practical implications include developing adaptive personalization strategies, improving data governance, and fostering transparent communication to strengthen consumer trust and long-term relationships. Organizations should integrate AI insights with customer-centric strategies to enhance competitive advantage sustainably. Novelty: This study aims to synthesize existing literature to provide a comprehensive understanding of the relationships between hyper-personalized content, artificial intelligence, consumer engagement, and purchase decisions in digital marketing.